The horizontal deformation analysis of high-rise buildings - Gražulis, Žymantas; Krikštaponis, Boleslovas; Neseckas, Algirdas; Popovas, Darius; Putrimas, Raimundas; Šlikas, Dominykas; Zigmantienė, Evelina (International Conference “Environmental Engineering”, 2017)
The horizontal deformation analysis of high-rise buildings, quite often is complicated because buildings like chimneys, towers and etc, have complex and asymmetric shapes, consequently there is not always the possibility to apply the method of single points motion analysis. Furthermore, the horizontal deformation analysis is complicated using standard measurement methods like measurements with electronic total stations or optical theodolites. In such case the terrestrial laser scanner could be superior to traditional measurements. However, the terrestrial laser scanner still not widely used to survey building horizontal deformations using high precision measurements. The main aim of this work is to determine the suitability to measure deflections of buildings from the vertical using terrestrial laser scanners and to investigate point cloud data processing. Measurements of horizontal deformation were carried out using the over ground laser scanner and electronic total station. Horizontal deformations of chimneys of thermal power plants were investigated using corresponding methods. Deformation indicators and evaluated measurement accuracies between different methods were compared. Data analysis of terrestrial laser scanning is more complex, time consuming and requires sophisticated hardware resources in comparison with the traditional methods, however results are much more detailed and informative.
Keywords: deformations; vertical deflection of buildings; terrestrial laser scanner; geodetic observations